(untitled) (Superficies y Vacío, 2014)
The application of traditional surface modification techniques to improve mechanical properties of a wide range of materials has been used for at least three decades with important results. More recently, newer and innovative techniques such as Laser Shock Processing (LSP) have gained popularity due to the benefits offered. In this work, Ti6Al4V alloy was treated under several conditions of laser density and wavelength during the treatment. The roughness of the samples before and after treatment was measured by perfilometry. The resultant surface roughness average (Ra) is in the range for biomedical implants. The microhardness values were taken from the sample cross-section showing no increment after being treated with LSP. X-ray diffraction (XRD) was used for phase identification and possible changes in the lattice parameters. The abrasive wear resistance was evaluated by means of ball cratering tests, the wear volume was assessed measuring wear scars using profilometry from which the wear rate was calculated. Samples treated with LSP were in some cases more susceptible to abrasive wear that the untreated material.